2015
DOI: 10.1097/j.pain.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

High- and low-frequency transcutaneous electrical nerve stimulation does not reduce experimental pain in elderly individuals

Abstract: High- and low-frequency transcutaneous electrical nerve stimulation is effective for reducing experimental heat pain in young individuals but not in older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
3
23
0
3
Order By: Relevance
“…The frequency of stimulation may be a key factor. Although there are different studies of nerve stimulation for neuropathic pain showing good results in reducing hyperalgesia by applying different frequencies , we focused in 50 Hz because is the most commonly used for pain therapies in the clinic and has been validated in preclinical models of neuropathic pain (see ) and supported by our preliminary assays. Alternating the frequencies of stimulation induces a variation in the pain thresholds and high frequencies are known to be able to block conduction in C‐fibers .…”
Section: Discussionmentioning
confidence: 98%
“…The frequency of stimulation may be a key factor. Although there are different studies of nerve stimulation for neuropathic pain showing good results in reducing hyperalgesia by applying different frequencies , we focused in 50 Hz because is the most commonly used for pain therapies in the clinic and has been validated in preclinical models of neuropathic pain (see ) and supported by our preliminary assays. Alternating the frequencies of stimulation induces a variation in the pain thresholds and high frequencies are known to be able to block conduction in C‐fibers .…”
Section: Discussionmentioning
confidence: 98%
“…There are some difficulties due to multiple comorbidities and polypharmacy in the treatment of pain in elderly individuals. Previous studies have reported that TENS application, which is given in different current intensities (low-intensity and highintensity) decreased pain (Bjordal, Johnson & Ljunggreen, 2003;Johnson & Martinson, 2007;Claydon et al, 2011;Bergeron-Vézina et al, 2015). This beneficial effect of TENS was important in the nonpharmacological treatment of the pain in the elderly subjects who prone to pharmacological side-effects (Chabal et al, 1998;Elvir-Lazo & White, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…A TENS at 80 pulses per second (80 Hz) has been shown to increase the pain threshold related to pressure algometry in healthy participants [10]. Furthermore, a recent randomized, double-blind crossover study also indicated that 100 Hz and 3 Hz TENSs all increased the pain thresholds of young individuals [11]. All the abovementioned results demonstrated that a higher-frequency TENS is better than a conventional low-frequency TENS.…”
Section: Introductionmentioning
confidence: 97%